2003
DOI: 10.1021/jp026287z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Oxidative Degradation of Azo Dyes:  A Density Functional Theory Study

Abstract: In this paper, we show, using DFT methods, reactivity indices, and electron density topology, that oxidative degradation of azo dyes occurs through the cleavage of the N-N bond following hydroxyl radical addition to the chromophore. Structures for both experimentally proposed reaction pathways, involving either cleavage of the C-N or N-N bonds, have been optimized at the B3LYP/6-31G(d) level of theory; the energies were further refined using single point calculations at the B3LYP/6-311+G(d,p)//B3LYP/6-31G(d) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 92 publications
4
43
0
1
Order By: Relevance
“…The more accepted mechanism is outlined in Scheme 1. In outset, azo bond is oxidative cleavage either C-N or N-N cleavage by attaching the hydroxyl radical that generated via photocatalysis process [40] …”
Section: Suggested Mechanismmentioning
confidence: 99%
“…The more accepted mechanism is outlined in Scheme 1. In outset, azo bond is oxidative cleavage either C-N or N-N cleavage by attaching the hydroxyl radical that generated via photocatalysis process [40] …”
Section: Suggested Mechanismmentioning
confidence: 99%
“…Instead of C-N cleavage, N-N cleavage accompanying with the formation of nitroaromatics has also been proposed as the main process (60%) in the ultrasonic degradation of azo dyes initiated by the attack of • OH as well [62]. Based on quantum mechanical molecular orbital calculations using density functional theory, it has been proposed that oxidative degradation of amino-substituted azo dyes occurred through cleavage of N-N bond, following the • OH radical addition to the chromophore [63]. It was suggested that the presence of hydrazone tautomers might be responsible for the involvement of C-N cleavage in the degradation of azo dyes.…”
Section: Steady State Radiolysismentioning
confidence: 99%
“…Most of the reported experimental works have been performed in aqueous aerated acidic or alkaline solutions. The decrease of absorbance with irradiation, bleaching, suggests that it can be use as a chemical dosimeter [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%